Effects of electroacupuncture on bladder dysfunction and the expression of PACAP38 in a diabetic rat model - Han, Xuke; Chen, Yiding; Ha, Lue; Yang, Jiao; Wang, Fangzhou; Chen, Huizhen; Zhou, Qian; Long, Cong; Qiu, Xianliang; Chen, Qiu (Frontiers in Physiology, 2023)
Objective: To explore the effects and the possible mechanism of electroacupuncture (EA) on diabetic bladder dysfunction (DBD) in streptozotocin-high fat diet (STZ-HFD) induced type 2 diabetes mellitus (T2DM) rats. Methods: The experiment was divided into Control, DBD, EA, and Sham EA group. After eight weeks of EA intervention, the body mass, 24 h urine volume, intraperitoneal glucose tolerance test (IPGTT), and urodynamics were detected. After the wet weight of the bladder was detected, the hematoxylin-eosin (HE), Masson's trichrome, and TUNEL were used to analyze histological changes. The PACAP38 expressions in the bladder were detected by Real-time PCR and Western blot. Results: Compared to the Control group, the bladder wet weight, 24 h urine volume, blood glucose, maximum bladder capacity, bladder compliance, bladder wall thickness, the smooth muscle/collagen ratio, and apoptosis rate of the DBD group were significantly increased. Moreover, the body mass and leak point pressure were significantly reduced. Compared with the Sham EA group, the bladder wet weight, maximum bladder capacity, bladder compliance, bladder wall thickness, and apoptosis rate of the EA group were significantly reduced. In contrast, the leak point pressure was increased. The PACAP38 mRNA and PACAP38 protein expression of the DBD group were significantly lower than the Control group, while EA treatment could upregulate PACAP38 mRNA levels and PACAP38 protein expression of DBD model rats. Conclusion: EA could ameliorate bladder dysfunction in the DBD model rats by reversing bladder remodeling, which might be mainly mediated by regulating the PACAP38 level.